2022
DOI: 10.1038/s41467-022-33252-6
|View full text |Cite
|
Sign up to set email alerts
|

Small soluble α-synuclein aggregates are the toxic species in Parkinson’s disease

Abstract: Soluble α-synuclein aggregates varying in size, structure, and morphology have been closely linked to neuronal death in Parkinson’s disease. However, the heterogeneity of different co-existing aggregate species makes it hard to isolate and study their individual toxic properties. Here, we show a reliable non-perturbative method to separate a heterogeneous mixture of protein aggregates by size. We find that aggregates of wild-type α-synuclein smaller than 200 nm in length, formed during an in vitro aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 70 publications
1
83
0
Order By: Relevance
“…Results of a recent study by Emin et al [ 65 ] point to the most toxic types of synuclein aggregates. The authors developed a modification of α-synuclein aggregation reactions in the test tube with subsequent separation of aggregates by size.…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a recent study by Emin et al [ 65 ] point to the most toxic types of synuclein aggregates. The authors developed a modification of α-synuclein aggregation reactions in the test tube with subsequent separation of aggregates by size.…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
“…Further experiments demonstrated that the soluble aggregates from PD patients’ brains were smaller and more inflammatory than the large aggregates in control brains. The authors conclude that the small non-fibrillar α-synuclein aggregates are the critical species causing neuroinflammation and disease progression [ 65 ].…”
Section: Synuclein-based Methods Of Disease Diagnosismentioning
confidence: 99%
“…Furthermore, there can be a variety of types of aggregates, and whether and which aggregates are causing disease is still not fully clear. A recent study demonstrated that it is actually small soluble α-syn aggregates that cause toxicity to cells, and these resemble those found in the post-mortem patient’s brain [ 193 ]. A major question is also how a single protein is causing a spectrum of diseases.…”
Section: Conclusion and Futurementioning
confidence: 99%
“…10 Prots et al demonstrated that αSyn oligomers disrupt axonal integrity in human neurons and that increased αSyn oligomerization by expressing oligomer-forming mutants (E46K and E57K) of αSyn resulted in impaired axonal transport of mitochondria. 11 Although most soluble oligomeric species of αSyn are toxic, 9 the molecular basis of toxicity remains to be established. 12 Therefore, the biophysical characterization of αSyn oligomers is essential for understanding their pathology and developing therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%